Acute cough in Italian children: parents’ beliefs, approach to treatment, and the family impact - Dal Negro, Roberto W. (Multidiscip Respir Med, 2019)
BACKGROUND: Acute cough is the most common symptom among children in primary care, but the impact of cough episodes was never investigated in Italian families. METHODS: A cross-sectional telephone survey was conducted on a representative sample of Italian families, randomly selected from general population; a specific and validated questionnaire was used. RESULTS: The sample (604 calls) was uniform by geographical distribution, and by children age and gender. Mean cough episode was 3.1/year, they were short lasting (only 4.7% > 2 weeks). Independent predictors of children cough episodes were parents’ active smoking habit and work (p < 0.05). The mean nursery/school absenteeism was mostly < 7 days, but of a 7–15-day duration in near 30% of cases. The pediatrician was contacted immediately only by 25% of parents and a second consultation (mostly a lung physician) usually occurred after 2–3 weeks of cough. Meanwhile, home/pharmacist suggested remedies were adopted in 50–70% of cases. Usual prescriptions were mucolytics (85.8%), antitussive agents (55.6%), non-steroideal anti-inflammatory drugs (33.8%), antibiotics (regularly or episodically 80%), and corticosteroids (systemic steroids in less than 50%, but via aerosol in more than 80% of cases). Moreover, pediatricians claimed to use homeopathic drugs regularly or episodically in almost 50%. The respondents’ willingness to spend out-of-pocket for an “effective remedy” against cough was of € 20 (>€ 30 in 18.4% of cases). CONCLUSIONS: Parents’ actions against cough episodes were variable, depending on their beliefs, smoking habit, and occupational status. The parents’ perceived efficacy of usual prescriptions is poor, and their willingness to pay out-of-pocket for an “effective remedy” against cough is high. The interest for alternative treatments is not negligible in these circumstances. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s40248-019-0180-9) contains supplementary material, which is available to authorized users.